Mind the gap : the mediating role of mindful marketing between market and quality orientations, their interaction, and consequences - Malhotra, Naresh K. (2013)
Purpose – The purpose of this paper is to integrate the distinctive streams of research on market orientation, quality orientation, and organizational mindfulness, and examine the mediating role of mindful marketing between market orientation and quality orientation, and their linkages to two emerging key outcomes: mindful consumption and value co-creation.